Measuring Up: A Comparison of TapeStation 4200 and Bioanalyzer 2100 as Measurement Tools for RNA Quality in Postmortem Human Brain Samples - Walker, Jessica E.; Oliver, Javon C.; Stewart, Analisa M.; Beh, Suet Theng; Arce, Richard A.; Glass, Michael J.; Vargas, Daisy E.; Qiji, Sanaria H.; Intorcia, Anthony J.; Borja, Claryssa I.; Cline, Madison P.; Hemmingsen, Spencer J.; et al. (International journal of molecular sciences, 2023)
The determination of RNA integrity is a critical quality assessment tool for gene expression studies where the experiment’s success is highly dependent on the sample quality. Since its introduction in 1999, the gold standard in the scientific community has been the Agilent 2100 Bioanalyzer’s RNA integrity number (RIN), which uses a 1–10 value system, from 1 being the most degraded, to 10 being the most intact. In 2015, Agilent launched 4200 TapeStation’s RIN equivalent, and reported a strong correlation of r2 of 0.936 and a median error < ±0.4 RIN units. To evaluate this claim, we compared the Agilent 4200 TapeStation’s RIN equivalent (RINe) and DV200 to the Agilent 2100 Bioanalyzer’s RIN for 183 parallel RNA samples. In our study, using RNA from a total of 183 human postmortem brain samples, we found that the RIN and RINe values only weakly correlate, with an r2 of 0.393 and an average difference of 3.2 RIN units. DV200 also only weakly correlated with RIN (r2 of 0.182) and RINe (r2 of 0.347). Finally, when applying a cut-off value of 6.5 for both metrics, we found that 95.6% of samples passed with RIN, while only 23.5% passed with RINe. Our results suggest that even though RIN (Bioanalyzer) and RINe (TapeStation) use the same 1–10 value system, they should not be used interchangeably, and cut-off values should be calculated independently.